Proceedings of the 3rd Annual International Conference on Mechanics and Mechanical Engineering (MME 2016) 2017
DOI: 10.2991/mme-16.2017.67
|View full text |Cite
|
Sign up to set email alerts
|

Thermogravimetric Assessment of Combustion Characteristics of Blends of Lignite Coals with Coal Gangue

Abstract: Abstract. In this paper, the co-combustion behaviour of lignite coal with coal gangue and coal are investigated by a thermogravimetric analysis (TGA) in the temperature range from ambient temperature to 1000 ℃. The thermal characteristics and kinetics of lignite coal, coal gangue and their blends are evaluated under combustion conditions using a non-isothermal thermogravimetric method (TGA). Lignite coal is blended with coal gangue in the range of 25-75 wt. % to evaluate their cocombustion behaviour. Such atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Based on these results, it can be concluded that the oxy‐cracked petcoke is more ignitable, reactive, flammable, combustible, easier to oxidize, and has less pollutant than the virgin petcoke. It was reported that the materials with the highest values of Di, Df,Ss, and FI may be advantageously used for blending with other fuel . Therefore, mixing such ignitable and effective material with a currently‐used fuel would be a promising approach for saving consumed energy and reducing the emitted gases.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…Based on these results, it can be concluded that the oxy‐cracked petcoke is more ignitable, reactive, flammable, combustible, easier to oxidize, and has less pollutant than the virgin petcoke. It was reported that the materials with the highest values of Di, Df,Ss, and FI may be advantageously used for blending with other fuel . Therefore, mixing such ignitable and effective material with a currently‐used fuel would be a promising approach for saving consumed energy and reducing the emitted gases.…”
Section: Resultssupporting
confidence: 73%
“…Another important feature of the fuel is the flammability index (FI). The FI reflects the fuel combustibility; the higher FI is, the better the fuel's combustibility is, and can be determined by the following equation: FI=normalRnormalmaxnormalTnormali2…”
Section: Experimental Workmentioning
confidence: 99%
See 1 more Smart Citation
“…[48]. Therefore, impacts on coal structural intactness, density and fracture toughness are comprehended from the plot-skewness and pattern irregularity echoed via peak-de ection intensity data or the diffraction patterns suggested large quantity of the amorphous phases being detected hence plot broadness and sloping which are not easily mapped highlighted numerous phase irregularity and orientation-variance with a short time interval [38], [49].…”
Section: Xrdmentioning
confidence: 99%
“…In order to have a better overview of the different combustion characteristics, three integrated indexes were computed [39,40].The ignition index (D i ) is calculated using Equation (2):…”
Section: Yield (%) =mentioning
confidence: 99%